Model Pembelajaran RADEC dengan Media Interaktif untuk Meningkatkan Literasi dan Kemampuan Berpikir Kritis dalam Pembelajaran Geografi - Siti Rohani; Syafri Anwar; Dedi Hermon; Bayu Wijayanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in improving students’ literacy and critical thinking skills in geography learning at the senior high school level. The need for this research arises from the consistently low literacy and higher-order thinking performance of Indonesian students in PISA and AKM, as well as the limited implementation of RADEC in geography. This study employed a one-group pretest–posttest quasi-experimental design involving 16 eleventh-grade students from SMA Negeri 3 Tebing Tinggi Barat, Riau Province. The instruments consisted of a literacy test based on AKM indicators and a critical thinking test adapted from Facione’s framework, which measured Interpretation, Analysis, and Evaluation. Data were analyzed using descriptive statistics, N-gain calculations, and paired-samples t-tests. The results showed a significant improvement (p < 0.05) in both variables, with N-gain scores of 0.40 for geographic literacy and 0.36 for critical thinking, categorized as moderate. These findings indicate that the RADEC model enhances students’ literacy and critical thinking through structured stages involving reading comprehension, answering tasks, collaborative discussion, explanation, and the creation of learning products. The study provides empirical evidence for the application of RADEC in geography learning and highlights its relevance to the Merdeka Curriculum.